Compilation of Parameter Control for Mapping the Potential Landslide Areas - P. A. Maha Agung; M. F. Rouf Hasan; Adi Susilo; Mustaffa A. Ahmad; Mohd. J. Bin Ahmad; U. A. Abdurrahman; A. T. Sudjianto; Eko Andi Suryo (Salehan Institute of Higher Education, 2023)
Batu Tourism City is located in a mountainous area, so based on information from the BNPB, it has quite a large potential for landslides. Landslide hazards can frequently disrupt public traffic due to road cuts. Landslide mapping digitally will contribute to handling and mitigation activities since the database can be updated in real time to anticipate landslide hazards. This study aims to map landslide-prone areas located in the Payung zone, Songgokerto Village, and Batu City. Landslide areas can be determined by mapping analysis using GIS software. GIS can determine the classification level for a landslide susceptible area. Some input data that will influence landslides, such as rainfall, wind, earthquakes, etc., was collected as the control parameters. All parts of the study area could be classified as areas with minor, medium, and major potential for landslides. Primary data are collected from geo-surveying (aerial images) using drone devices for interpretation of landslide susceptibility areas, geophysical to identify the type of soil or rock layers that completed their behavior, and slip planes as well using geo-electric, geotechnical engineering to predict slope stability with the correlation from cone penetration test (CPT) data, and geo-hydraulic to observe the rainfall and the catchment area model using the available secondary data. Geometrically, measurement data found that the average slope angle at the upper and lower of the East Java Province highway is around 40–50o. Studies from geophysical data identified that the hilly terrain in the object study area has been dominated by the weathered rock layer. Geotechnical data obtained shows the soil layers at the slope location will be stable with the water content under 35% during the dry season and may become unstable with the water content reaching over 50% due to the increase in saturation during the rainy season. The landslide that occurred was more caused by seepage behavior from surface water flow towards the sloping plane, and then the safety factor during the rainy season reached the critical values at SF = 0.58. During the dry season, the unsaturated process due to the temperature change generates a safety factor (SF) of more than 1.2. The compilation data produced maps of susceptible landslides and surface flow distribution. Doi: 10.28991/CEJ-2023-09-04-016 Full Text: PDF